Angular for material design : leverage Angular material and TypeScript to build a rich user interface for web apps - Kotaru, Venkata Keerti (Apress, 2020)
Build Angular applications faster and better with TypeScript and Material Design. You will learn how to build a web interface and use Google's open source Angular Material library of ready-made and easy-to-use components. This book uses Angular with TypeScript (a superset to JavaScript) to enable use of data types and take advantage of programming constructs such as classes, interfaces, generic templates, and more. You also will utilize various Angular features, including data binding, components, services, etc. You will build a single page application with the help of routing capabilities available out of the box (Angular CLI) and interface with remote services over HTTP. What You Will Learn Build an application using Angular, TypeScript, and Angular Material Understand Angular concepts such as components, directives, services, and more Use TypeScript features, including data types, classes, interfaces, generic templates, etc. Build a single page application (SPA) with routing features and integrate it with server-side remote services Who This Book Is For Beginning to intermediate level professionals will learn about web development using Angular, TypeScript, and Angular Material. Patterns and practices are recommended to be a successful developer. Basic knowledge of JavaScript is helpful.